Lithuanian case study of masonry buildings from the Soviet period - Brauers, Willem Karel M.; Kracka, Modestas; Zavadskas, Edmundas Kazimieras (Journal of Civil Engineering and Management, 2012)
This paper presents the process of effective selection of building elements for renovation important for energy saving in buildings. A large part of energy is lost in non-effective buildings. Therefore, in renovation of buildings, it is important to select effective structural improvements. Building insulation could not only save energy but also time, money and materials, which means that different objectives expressed in different units have to be fulfilled. Although different methods exist for the application of Multi Objective Optimisation, MULTIMOORA, which is composed of three sub-methods – Ratio System, Reference Point Method that uses ratios from the ratio system, and the Full Multiplicative Form – was preferred. Consequently, different solutions for building envelope renovation were ranked by MULTIMOORA as applied for masonry buildings from the Soviet period.